DNA binding to zwitterionic model membranes - Ainalem, Marie-Louise (Langmuir : the ACS journal of surfaces and colloids, 2010)
This study shows that DNA (linearized plasmid, 4331 base pairs and salmon sperm, 2000 base pairs, respectively) adsorbs to model membranes of zwitterionic liquid crystalline phospholipid bilayers in solutions containing divalent Ca(2+) cations, and also in solutions containing monovalent Na(+). The interaction between DNA and surface-supported model membranes was followed in situ using null ellipsometry, quartz crystal microbalance with dissipation, as well as neutron reflectometry. In the presence of Na(+) (in the absence of multivalent ions), DNA adopts an extended coil conformation upon adsorption. The solvent content in the adsorbed layer is high, and DNA is positioned on top of the membrane. In the presence of divalent Ca(2+), the driving force for the adsorption of DNA is electrostatic, and the adsorbed DNA film is not as dilute as in a solution containing Na(+). Cryo-TEM and SANS were further used to investigate the interaction in bulk solution using vesicles as model membrane systems. DNA adsorption could not be identified in the presence of Na(+) using SANS, but cryo-TEM indicates the presence of DNA between neighboring unilamellar vesicles. In the presence of Ca(2+), DNA induces the formation of multilamellar vesicles in which DNA intercalates the lamellae. Possible electrostatic and hydrophobic mechanisms for the adsorption of DNA in solutions containing monovalent salt are discussed and compared to the observations in divalent salt